Spectral Analysis and In Vitro Biological Activity of Cu(II) Complex with Tridentate ONO Schiff Base Ligand - Emir Horozić; Merima Ibišević; Darja Husejnagić; Enida Karić; Nusreta Hasić; Amina Hajdarević (The Journal of Pure and Applied Chemistry Research, 2021)
In this study, metal complex of Copper(II) with a Schiff base derived from 2,2-dihydroxyindane-1,3-dione and 2-aminoethanoic acid were synthesized. The product are characterized by spectral methods. The antimicrobial activity was tested on reference bacterial strains and the antioxidant capacity was analyzed by using the DPPH and FRAP methods. The spectral data indicates that the Schiff base coordinates the Copper(II) as a tridentate ONO donor ligand. The compounds showed weaker antimicrobial activity on certain tested microorganisms. In vitro testing of antioxidant activity showed a significant reducing ability of the complex, as well as inhibitory activity against DPPH radicals.